Fracture toughness of hydrogen charged as-quenched ultra-high-strength steels at low temperatures - Pallaspuro, S. (Sakari); Yu, H. (Haiyang); Kisko, A. (Anna); Porter, D. (David); Zhang, Z. (Zhiliang) (Elsevier, 2017)
Abstract The effect of hydrogen on the fracture and impact toughness of ultra-high-strength steels at sub-zero temperatures in the transition temperature region has been investigated with arctic applications in mind. Two types of as-quenched microstructure were studied, i.e. autotempered martensite and a mixture of martensite and bainite, both having yield strengths close to 1000 MPa. These were charged with hydrogen using passive cathodic protection and then tested in both the charged and uncharged condition at sub-zero temperatures. Hydrogen contents were measured with melt-extraction. Fractography, kernel average misorientation measurements and cohesive zone modelling were used to analyse the results considering the degree and the active mechanisms of hydrogen embrittlement. It is shown that hydrogen embrittlement is present at sub-zero temperatures, causing an increase in fracture toughness reference temperature T0 and a small decrease in deformation capability. The relationship between the T0 and the impact toughness transition temperature T28J, which, in the case of ultra-high-strength steel, deviates from that observed for lower strength steels, is proposed to be affected by the hydrogen content.